HUBUNGAN KONDISI LINGKUNGAN RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS TAMAN KABUPATEN SIDOARJO - Carina Delvi Trisiyah; Chatarina Umbul W (The Indonesian Journal of Public Health, 2018)
Pneumonia is the cause of 16% of underfive children deaths worldwide. The number of cases of pneumonia in Sidoarjo had been continued to increase from 2013-2015. This study aims to describe the condition of home environment with the incidence of pneumonia in underfive children. This research was descriptive observational study with case control study approach. The sample in this study consisted of 32 cases of underfive children who suffering ISPA pneumonia and 32 cases of ARI without pneumonia. The independent variables in this study were occupancy density, ventilation area, floor type, wall type, and cigarette smoke exposure. The results showed that underfive children who suffering ISPA pneumonia have high home density (68,8%), often exposed by cigarette smoke (75,0%), and ventilation respondents was not eligible (100,0%). Based on the results of this study, the parents should to change the behavior not to smoke in their home. In addition, they should get used to open the door of their house so the air circulation in the house can exchange well.